The Impact of Cyber Attack to the Performance of Indonesia's Sharia Bank Stocks in 2023 - Hamdan Ardiansyah,; Arie Noviana,; Aip Zaenal Mutaqin, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
Cyberattacks on the financial sector, including Islamic banks, pose serious threats that can impact market stability and performance. This includes Bank Syariah Indonesia, the largest Islamic bank in Indonesia, where such risks may affect stock performance. This research aims to analyze the impact of cyberattacks on the stock performance of Bank Syariah Indonesia, both before and after the cyberattack incident. The methodology employed is quantitative analysis with comparative tests. The data used is secondary data obtained from Indonesia Stock Exchange (IDX) and Yahoo Finance. The sample was taken from the stock return data of BSI with the stock code BRIS for the year 2023, before and after the cyberattack. Data testing utilized normality tests and comparative tests using the Wilcoxon test. The results indicate a significance value above 0.05, specifically 0.852, suggesting that the stock returns before and after the cyberattack did not experience a significant difference. This indicates that BSI’s stock returns remained stable despite the cyberattack, with the market tending to focus on fundamental performance and long-term prospects of BSI’s stock. Thus, the occurrence of the cyberattack did not affect the stock return, which is part of the stock performance.